Development of Qur’an Education Through the Love Curriculum Using Wordwall at Tpq Aikal Bengkulu - Inestha Rahmadani; Masrifa Hidayani; Ela Nopri Manda Sari; Selindri; Aldo Sugiawan (Edumaspul: Jurnal Pendidikan, 2026)
Learning the Qur’an in early childhood is often faced with the challenge of boredom due to approaches that tend to be rigid and oriented solely to memorization targets. The community service activity through the Real Work Lecture (KKN) of Elementary School Teacher Education (PGMI) Group 14 students aims to develop Qur’an education through the Love Curriculum using Wordwall at TPQ Aikal, Sumur Dewa Village, Bengkulu. The Love Curriculum emphasizes a humanistic, compassionate, and psychologically comfort-centered pedagogical approach, while the Wordwall platform is implemented as a digital gamification medium to stimulate the active involvement of students. The implementation method of this service uses the Asset-Based Community Development (ABCD) approach to map and optimize the local potential of the TPQ institution. The program results show a significant transformation in students’ intrinsic motivation in reciting the Qur’an, an increase in the speed of understanding the makhorijul letter, and the creation of an inclusive and cheerful classroom atmosphere. Program evaluation using the Societal Impact Index (SII) resulted in an effectiveness score of 93.8% (very high category). The social impact of this development program includes increasing trust among students’ guardians in the existence of TPQ Aikal and the formation of a child-friendly and technology-based Al-Qur’an learning management model in Bengkulu